Perioperative pain management in elderly patients with а proximal femoral fracture: evidence review (Pain medicine, 2020)
The purpose of this article is to compare different methods of analgesia during perioperative period in elderly patients with а proximal femoral fracture. The incidence of hip fracture is high and also rises with the age, for example, In Great Britain, number of patients with a hip fracture will be approximately 100 000 in 2033, and it’s also associated with significant healthcare financing. Nevertheless, effective pain management is a big challenge for clinicians because of considerable problems in geriatric patients, including age, physiological changes in the elderly, preexisting comorbidities, cognitive impairment, high risk of delirium, problems with rehabilitation and probability of an independent life [12].   Opioids are still the main option for hip fracture pain management, despite differences in pharmacokinetics and pharmacodynamics in elderly patients, which are correlated with high frequency of side effects. Opioid-related adverse drug events are associated with worse patient outcomes such as morbidity, mortality and length of stay increase. Therefore, peripheral nerve blocks as part of multimodal analgesic technique can provide more effective pain control after hip fracture. Comprehensive literature searches focus on the use of peripheral nerves blocks as preoperative analgesia, as postoperative analgesia or as a supplement to general anesthesia for hip fracture surgery.
Keywords: analgesia; femoral fracture; psoas compartment block; paracetamol; opioids; delirium